A new perspective on hanzi: Based upon the multi-dialectical analysis of the Four Ways of Writing. (March 2021) - Jeon, Guk-jo
This work is, most of all, designed to wrestle with taken-for-granted explanations as to how hanzi is composed and in what ways the composition the Four Ways of Writing (四書) can be analysed. Beginning with posing a self-reflective question on the academic identities of us, the hanzi civilisation researchers, and looking for a possible answer to it within the context of an Eagletonian conceptualisation of human animality or creatureliness, the work then methodologises the multi-dialectical analysis by virtue of méta-linguistique, transduction, and abstraction concreté . The full-scale analysis of the Four Ways of Writing comes next, taking four steps: first, synthesising the existing definitions, explanations and interpretations of them; second, abstracting the synthesis up to the multi-dialectical analysis; third, introducing a topology of the Four Ways of Writing; and fourth, analysing characters related to and expanding from two radical characters of 門 and 刀 with the aid of a dynamics of trialectics between the form, sound and meaning. Resting upon all the analyses performed, the work suggests the following conclusion. Amongst hanzi's main characteristics is morphographicality (表形性), still the most distinctive within the analytical framework of the Four Ways of Writing. It is the very form of hanzi, as a matter of fact, that also turns out to be multi-dialectical: first, that which constitutes writing as the character trialectically related with both the sound and meaning; second, that which characterises writing as écriture of the dialectical relationship between human beings and nature; and last, that which dialectically elucidates who we are and what we are capable of.